Pengaruh Model Pembelajaran Predict Observe Explain (POE) Terhadap Hasil Belajar IPA Fisika Siswa SMP Negeri 1 Lembar Tahun Ajaran 2015/2016 - Elistiana Safitri; Kosim Kosim; Ahmad Harjono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
The aim of this research is to know the effect of using Predict Observe Explain (POE) method toward studentsÃ¢â¬â¢ achievement in Physics. This is an experimental research by using experimental group and control group. The research design was Post-test Only Control Group Design. The population of this research was the students of class VII SMPN 1 Lembar academic year 2015/2016. The sampling technique was Cluster Random Sampling in which class VII 2 as the control group and class VII 3 as the experimental group. Both of the groups were given a pre-test before the treatment to know the homogeneity of the groups. The instrument used is an objective test in form of multiple choices. The finding showed that the mean of the posttest in experimental group was 70 and the control group was 60.67, in which both of them were distributed normal and homogeneous. The post-test result was analyzed by using t-test (t-test polled variants) in which the value of the was 2.473 and the ÃÂ was 2.015 with dk=46 and the significant level was 5%. It showed that the was accepted and was rejected. Therefore, it can be concluded that Predict Observe Explain (POE) Method gave significant effect to the studentsÃ¢â¬â¢ achievement in Physics at Class VII SMPN 1 Lembar Academic year 2015/2016.